2022
DOI: 10.3390/biomedicines10071607
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antibacterial Activity of a Cationic Macromolecule by Its Complexation with a Weakly Active Pyrazole Derivative

Abstract: Molecules containing the pyrazole nucleus are widely reported as promising candidates to develop new antimicrobial compounds against multidrug-resistant (MDR) bacteria, where available antibiotics may fail. Recently, aiming at improving the too-high minimum inhibitory concentrations (MICs) of a pyrazole hydrochloride salt (CB1H), CB1H-loaded nanoparticles (CB1H-P7 NPs) were developed using a potent cationic bactericidal macromolecule (P7) as polymer matrix. Here, CB1H-P7 NPs have been successfully tested on se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…In cytotoxicity experiments at 24 h of exposure which were carried out by treating HaCaT cells with CB1H, CB1H-P7 and P7 NPs, we observed that NPs caused a significant reduction in cell viability only over concentrations of 1.43 µM [ 23 ]. So, in this case, the cytotoxic activity of the CB1H as a function of its concentrations was investigated using a wider concentration range (1–100 µM).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In cytotoxicity experiments at 24 h of exposure which were carried out by treating HaCaT cells with CB1H, CB1H-P7 and P7 NPs, we observed that NPs caused a significant reduction in cell viability only over concentrations of 1.43 µM [ 23 ]. So, in this case, the cytotoxic activity of the CB1H as a function of its concentrations was investigated using a wider concentration range (1–100 µM).…”
Section: Resultsmentioning
confidence: 99%
“…The selectivity of the cytotoxic activity of the tested compounds against tumor cells (cytotoxic properties) was estimated by selectivity indices (SI). The SI values were determined using the IC 50 , as was previously reported for the same compounds against normal human keratinocytes (HaCaT) [ 23 ] and according to Equation (1). …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations